Towards an Embodied Abstraction: An Historical Perspective on Lucinda Childs’ Calico Mingling (1973) - Lou Forster (Arts, 2021)
In the 1970s, choreographer Lucinda Childs developed a reductive form of abstraction based on graphic representations of her dance material, walking, and a specific approach towards its embodiment. If her work has been described through the prism of minimalism, this case study on Calico Mingling (1973) proposes a different perspective. Based on newly available archival documents in Lucinda Childs’s papers, it traces how track drawing, the planimetric representation of path across the floor, intersected with minimalist aesthetics. On the other hand, it elucidates Childs’s distinctive use of literacy in order to embody abstraction. In this respect, the choreographer’s approach to both dance company and dance technique converge at different influences, in particular modernism and minimalism, two parallel histories which have been typically separated or opposed.